Profil Pasien Operasi Vitreoretinal di Instalasi Bedah Sentral RSUP Prof. Dr. R. D. Kandou Manado Periode Juli 2018 – Juli 2019 - Boedihardjo, Gita P.; Sumual, Vera; Najoan, Imelda (e-CliniC, 2019)
Abstract: Retinal disorders are ranked as the fourth most common eye disease in Indonesia. Retinal and vitreous disorders can cause severe visual impairment and even blindness. This study was aimed to determine the profile of patients undergoing vitrectomy at the Central Surgical Installation of Prof. Dr. R. D. Kandou Hospital Manado form July 2018 - July 2019. This was a retrospective and descriptive study using medical record data of vitreoretinal surgery patients. The results showed that there were 31 patients who underwent vitreoretinal surgery, consisting of 16 males (51.6%) and 15 females (48.4%). Based on the type of surgery; vitrectomy was performed on 15 patients (48.4%); vitrectomy + laser photo-coagulation on 7 patients (22.7%); vitrectomy + injection of gas dan silicon oil on 3 patients (9.7%); and 2 patients each (6.4%) for gas and silicon oil injection, laser photocoagulation, and vitrectomy + gas injection and silicon oil + laser photocoagulation. In conclusion, the most common type of surgery was vitrectomy based on retinal detachment. Most patients were retired and at the age of 46-65 years.Keywords: vitreoretinal surgery, vitreoretinal abnormalities, vitrectomy, retinal detachment Abstrak: Gangguan retina berada di urutan ke empat sebagai penyakit mata terbanyak di Indonesia. Bila terjadi gangguan pada retina dan vitreous bisa menimbulkan gangguan penglihatan yang berat bahkan kebutaan. Penelitian ini bertujuan untuk mengetahui profil pasien yang menjalani operasi vitreoretinal di Instalasi Bedah Sentral RSUP. Prof. Dr. R. D. Kandou Manado periode Juli 2018 – Juli 2019. Jenis penelitian ialah deskriptif retrospektif dengan menggunakan data rekam medik pasien operasi vitreo retina. Hasil penelitian mendapatkan 31 pasien yang menjalani operasi vitreoretinal, dengan jenis kelamin laki-laki sebanyak 16 pasien (51,6%) dan perempuan 15 pasien (48,4%). Berdasarkan jenis operasi diperoleh data vitrektomi pada 15 pasien (48,4%), vitrektomi + laser fotokoagulasi 7 pasien (22,7%), vitrektomi + injeksi gas dan silicon oil 3 pasien (9,7%), dan masing-masing 2 pasien (6,4%) untuk jenis operasi injeksi gas + silicon oil, jenis operasi laser fotokoagulasi, dan vitrektomi + injeksi gas dan silicon oil + laser fotokoagulasi. Simpulan penelitian ini ialah jenis operasi yang terbanyak dilakukan yaitu vitrektomi, dengan indikasi ablasio retina. Sebagian besar pasien berada pada kategori usia 46-65 tahun, dengan pekerjaan pensiunan.Kata kunci: operasi vitreo retina, kelainan vitreo retina, vitrektomi, ablasio retina